Revisiting the identity and distribution of Allspice (Myrtaceae), a misidentified spice in India - Nissar, Vettathukattil Abdulgafoor Muhammed; Rajagopal, Sivaranjani; Cheruppoyilath Mana , Harinarayanan; Thotten Elampilay, Sheeja; Illathidath Payatatti, Vijesh Kumar; Prabhukumar, Konickal Mambetta; Jagadamma, Rema; Saji, Koryampallil Vijayan (Phytotaxa, 2024)
Our recent studies revealed that the species being grown throughout India as ‘Allspice’ is not Pimenta dioica but an allied species, P. racemosa or Bay rum tree. We could locate true allspice (P. dioica), only at a single location in southern India. P. racemosa can be distinguished by its five lobed calyx and corolla and slightly larger fruits with 3–6 seeds in place of four lobed calyx and corolla and smaller fruits with 1–2 seeds in P. dioica. To elucidate its identity and to avoid the trade of a commodity under an erroneous name, the morphological, anatomical and molecular characters delineating the two species are studied and the distribution of the genus Pimenta in India is discussed here.